Principles of and Approach to Chronic Disease Management – An Overview - Morgan, Hue (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Chronic diseases such as Ischaemic Heart Disease and Stroke, Type 2 Diabetes, COPD/Asthma and Hypertension are all increasing in the developing world. In the coming years they will impose an increasing burden on the health care systems of all developing countries, where they are already a leading cause of mortality.1 Clear evidence exists for the best way of managing these diseases to reduce patient morbidity and mortality. The challenge is how to implement such management in a realistic way with limited resources, particularly targeting the most vulnerable patient groups such as poor and rural populations